Development of a soft UV-NIL step&repeat and lift-off process chain for high speed metal nanomesh fabrication. (10th June 2020) - Haslinger, M J; Mitteramskogler, T; Kopp, S; Leichtfried, H; Messerschmidt, M; Thesen, M W; Mühlberger, M
Abstract: In this work, we present a fabrication procedure of metal nanomesh arrays with the newly developed nanoimprint resist mr-NIL212FC used in a bi-layer resist system for a lift-off process. We comparatively analyzed and evaluated nanomeshes fabricated with a freshly prepared h-PDMS/PDMS stamp and a stamp used 501 times. Therefore, we first performed a step&repeat imprint test run in a self-built low cost step&repeat UV-NIL setup. We inspected the imprint behavior of the stamp, the UV-transmission through the stamp as well as stamp lifetime and stamp degradation with regard to the possible changes of its surface roughness. The nanomesh fabrication process is characterized by a good lift-off performance, leading to a low defect density of <1.26 defects 100 µ m −2 . Even after 501 imprints, only a negligible stamp degradation occurred without effecting the imprint performance. Likewise, the same holds true for the nanomeshes, which showed comparable low defect densities and feature sheet resistances of 3.54 ± 0.14 Ω/□ for the first and 3.48 ± 0.23 Ω/□ for the 501st nanomesh, respectively. AFM analyses further revealed that the maximum height of the roughness Rt changed over the course of the 501 imprints from 6.3 nm to 13.3 nm, representing <5% of the overall imprint height. In general, the mr-NIL212FC resist shows a good wettability and compatibility with standard h-PDMS/PDMS stamps, a fast curing behavior, a high replication fidelity, easy separation characteristics, and a very low diffusion of resist components into the stamp. The mr-NIL212FC resist allows exposure times as short as 2 s in the applied tool setup, enabling high throughput production. Moreover, all performed measurements indicate that a much higher number of imprints with one stamp seem possible.